Pelatihan Pemasaran Online Bagi Kelompok Usaha Bersama (KUB) â€œSRIKANDI" - Kurniawati, Emaya; Santoso, Aprih; Widowati, Sri Yuni (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2019)
Members of Kelompok Usaha Bersama (KUB) â€œSRIKANDIâ€ which is engaged in the health and food business so far its sales have not experienced an increase because its marketing is only carried out in the surrounding area or sold to close relatives and their own families, it requires a more productive marketing by using technological advances namely on-line marketing that utilizes the networkinternet to promote their products. The purpose of this Community Service program is to carry out online marketing training for Kelompok Usaha Bersama (KUB) â€œSRIKANDIâ€. The results of on-line marketing training are members of Kelompok Usaha Bersama (KUB) â€œSRIKANDIâ€ that can produce marketing and promotion on line for their production results widely so as to increase sales which will also have an impact on increase income of Kelompok Usaha Bersama (KUB) â€œSRIKANDIâ€